Social media used as a marketing public relations tool in Turkish football teams - (:unkn) unknown (My University, 2012)
Diğer bütün kurumlar gibi, futbol takımları da hedef kitleleri ve taraftarlarıyla etkileşim içerisine girmek için pazarlama amaçlı halkla ilişkilerden yararlanmaktadır. Yeni pazarlama yaklaşımında etkileşim, bağlantı kurma ve işbirliğinin önemli olması nedeniyle futbol takımlarının taraftarları ve diğer hedef kitleleriyle iletişimlerinde sosyal medya büyük bir öneme sahiptir .Bu yaklaşımla, çalışmada, Türk futbol liginde bugüne kadar şampiyon olan beş takımın sosyal medya kullanımları, pazarlama halkla ilişkilerinin uygulama alanları açısından incelenmektedir. Söz konusu futbol takımlarının sosyal medya uygulamalarından ürün tanıtımı, satış desteği, pazarlama desteği ve reklam desteği gibi amaçlarla pazarlama halkla ilişkilerinden yararlandıkları ve sosyal medya uygulamalarını Facebook ve Twitter hesapları aracılığıyla gerçekleştirdikleri görülmektedir.

Like any other organization, football teams began to use marketing public relations (MPR) as a marketing tool to interact with their publics and fans. Since the interactivity is an important component of the new marketing approach, social media can play an important role for the football teams to interact, connect and collaborate with their publics and fans. For the same reason, social media also became an important MPR tool for Turkish football teams. In this study, social media usage of the five of the Turkish football teams that have been champions will be discussed according to MPR purposes. After discussing the social media usage of those five football teams that have been champions according to four areas that MPR is practiced, it can be stated that those teams use all social media categories through their Facebook and Twitter accounts for their marketing public relations purposes such as product promotion, sales, marketing and advertising support.
Türk futbol takımlarında pazarlama halkla ilişkileri aracı olarak sosyal medya
Keywords: İletişim